Amplification dynamics of human-specific (HS) Alu family members. - Batzer, M A (1991)
We have investigated the distribution of several recently inserted Alu family members within representatives of diverse human groups. Human population studies using 65 unrelated human DNA samples, as well as a familial study to test inheritance, showed that individual Alu family members could be divided into three groups. The first group consisted of relatively older Alu family members which were monomorphic (homozygous) throughout the population tested (HS C3N1 and C4N6). The second group (HS C4N2, C4N5 and C4N8), apparently inserted into other repetitive regions of the genome, resulting in inconclusive results in the PCR test used. However, it is clear that these particular Alu insertions were present in a majority if not all of the loci tested. The third group was comprised of three dimorphic Alu family members (HS C2N4, C4N4 and TPA 25). Only a single Alu family member (TPA 25) displayed a high degree of dimorphism within the human population. This latter example also showed different allele frequencies in different human groups. The isolation and characterization of additional highly dimorphic Alu family members should provide a useful tool for human population genetics.